Laboratory Evaluation of the Combine Usage Possibilities of Entomopathogenic Nematodes with Insecticides against Mediterranean Corn Borer Sesamia nonagrioides (Lefebvre) - Erdem, Esenguel (Mdpi, 2024)
The Mediterranean Corn Borer (MCB), Sesamia nonagrioides, poses a significant threat to maize crops, necessitating effective pest management strategies. This study investigates the compatibility of two entomopathogenic nematode (EPN) isolates, Steinernema feltiae KV6 and Heterorhabditis bacteriophora EO7, with four registered insecticides for MCB control: deltamethrin, flubendiamide, spinetoram, and betacyfluthrin. The impact of these insecticides on EPN mortality, infectivity, and reproduction was assessed. Results indicate that deltamethrin exhibits the lowest toxicity to EPNs, with mortality rates of 1.3% for S. feltiae and 0.63% for H. bacteriophora at field dose (FD) after 24 h and 4.63% and 1.96%, respectively, after 48 h. In contrast, betacyfluthrin showed higher toxicity, with mortality rates of 38.04% and 14.17% for S. feltiae at 2FD and FD after 48 h. The infectivity assays demonstrated that deltamethrin-treated EPNs caused up to 100% mortality in MCB larvae, while the reproduction capacity varied significantly between the EPN species and insecticides. H. bacteriophora exhibited higher progeny production, especially in the presence of deltamethrin (87,900 IJs/larva). The findings suggest that integrating EPNs with selective insecticides like deltamethrin can enhance pest control efficacy and support sustainable agricultural practices. This study provides valuable insights for developing integrated pest management (IPM) strategies aimed at mitigating MCB infestations in maize while minimizing environmental impacts.
Keywords: entomopathogenic nematodes; Mediterranean Corn Borer; insecticides; compatibility